Adjustment without Transformation? Structural Adjustment Programs (SAPs), Deindustrialization, and Development Traps in Developing and Least-Developed Countries (LDCs) - Muhammad Haizul Falah (Jurnal Bisnis Mahasiswa, 2026)
Purpose – This paper examines whether Structural Adjustment Programs (SAPs) have facilitated structural transformation or merely achieved macroeconomic stabilization. Specifically, it investigates how SAP-driven liberalization and fiscal discipline relate to deindustrialization and the persistence of development traps in late-developing economies. The study aims to clarify whether adjustment reforms represent a pathway to productive upgrading or a mechanism of “adjustment without transformation.” Design/methodology/approach – The research adopts a qualitative comparative design grounded in historical political economy and structuralist analysis. It employs process tracing and institutional analysis across selected cases that experienced SAPs, deindustrialization, and persistent development traps. Empirical evidence is drawn from policy documents, international organization diagnostics, and contemporary academic literature (2018–2025). The analysis focuses on sequencing, coordination, and state capacity as mediating mechanisms linking SAPs to structural outcomes. Findings – The study finds that SAPs often replaced state-led industrial strategies without establishing alternative mechanisms for productive upgrading. Liberalization frequently preceded capability accumulation, exposing fragile industries to competition and leading to premature deindustrialization. The resulting structural shifts reinforced low-productivity equilibria and constrained development trajectories, suggesting that macroeconomic stabilization alone is insufficient for structural transformation. Research limitations – The qualitative design limits statistical generalizability and does not isolate causal effects quantitatively. Future research could combine longitudinal quantitative indicators with comparative case studies to test causal mechanisms and explore conditions under which adjustment and transformation coexist. Implications – The findings underscore the need to reintegrate industrial policy, strategic coordination, and state capacity into development strategies and conditional lending frameworks. They also call for reassessing SAP evaluation criteria beyond short-term stabilization. Originality – The paper advances the concept of “adjustment without transformation” by linking SAPs to long-term structural outcomes and development traps using recent empirical evidence and a structuralist theoretical lens.